The Role of Chemical Analysis in the Halal Authentication of Food and Pharmaceutical Products - Mursyidi, Achmad (Journal of Food and Pharmaceutical Sciences, 2013)
Food and pharmaceutical products (drugs and cosmetics) are one of the essential human needs since the human civilization. It is an obligation for Muslim to consume and use the halal consumer goods. Currently, there are numerous food and pharmaceutical products available in the market supplied to consumers in which the actual contents of these products are not clear; consequently, the halal verification and authentication of these are highly required. Non-halal items commonly found are pig derivatives such as pork, lard, and gelatin as well as alcohol (khamr), blood, dead meats, and the allowed animals to be consumed which are not slaughtered according to Syariah law. One of the ways to authenticate the halalness of the food and pharmaceutical products is chemical analysis which is relied to find the specific markers present or absent in the products they contain. Currently, some analytical techniques have been proposed and continuously developed for the authentication of halal products such as Fourier transform infrared (FTIR), chromatography-based methods, differential scanning calorimetry, electronic nose, and DNA-based methods. However, these methods can not verify the non-halal items which are not physical, chemical, or biological in nature like dead animal. Consequently, another method should be performed, i.e. direct and monitoring the production step (from farm to table). Besides, to succed the verification and authentication of halal products, passing the legislation of â€œHalal products assuranceâ€ by Indonesian parliament is urgently needed. Keyword: chemical analysis, food, pharmaceutical, halal authentication